MARKA OLUŞUMUNDA REKLAMIN YERİ - ÇAKAR, MEHMET FATİH (Fırat Üniveristesi, 2007)
Tüketicilerin her geçen gün piyasaya giren mal veya hizmetler arasında tercihte bulunurkengöz önünde bulundurdukları kriterlerin artması, üreticileri bu kriterler doğrultusunda üretimyapmaya ve iletişim tekniklerini kullanmaya zorunlu hale getirmiştir. Bu zorunluluklardanbirisi işletmelerin mal veya hizmetlerinin rakip mal ve hizmetler karşındaki belirleyicifarklarını ortaya koymada yararlandıkları pazarlama bileşenlerinin başında yer alan reklamdır.Günümüz tüketicisinin satın alma davranışının şekillenmesinde en büyük etkenlerden biriolan reklam, marka ve markaya yönelik olumlu tutumların oluşmasına önemli derecedehizmet etmektedir. Bu amaçla yapılan reklam çalışmalarında her öğenin kullanımının ayrı biröneminin olduğu tartışılmaz bir gerçektir. Bir markanın oluşumu ve markaya yönelik imajınoluşum sürecine bakıldığında her şeyden önce markanın tüketici zihninde net bir şekildekonumlandırılması gelmektedir. Bu sürecin seyrini ve hızını belirleyen de reklamdır.Reklamdan beklenen nihai amacın gerçekleştirmenin yanında, markaya yönelik olarak,tüketicilerin tutum düzeyleri, alışkanlıkları ve beklentileri dikkate alınarak yapılanuygulamalar markanın konumlandırılmasını kolaylaştıracaktır. Bu nedenle işletmelerinreklamlar aracılığı ile hedef kitleler üzerinde oluşturmaya çalıştıkları marka sadakati, markatutumu oluşum sürecini desteklemeleri, bunun sonucunda oluşacak güçlü markaları kendileriiçin daha sonra doğrudan bir reklam olacaktır. Reklamların tüketici davranışlarınıbelirlemedeki rolünün araştırıldığı bu araştırmada, uygulanacak reklam stratejileri ile markaoluşumuna reklamın katkısı araştırılmaya çalışılmıştır.Anahtar Kelimler: Marka, Tüketici, Reklam.

The image of a product or a service regarding consumers depends on some factors such as itsquality, reliability, customer satisfaction, advertising, though all activities performed underthis issue are in the framework of the brand itself. The brand, having strategic importanceregarding both the enterprises and the consumers, functions solely as a tool for advertisementfor enterprises. On the other hand, it confronts us as an indicator determining reliance, qualityand status in the view of consumers. Evolving ways of production and consumption has so farbrought some necessities. The increasing criteria that the consumers take into consideration inmaking preference among goods and service entering the market everyday, has long made itnecessary to produce in accordance with these criteria and to use communication techniquesfor the producers. One of these necessities is advertising, the first marketing component,which the enterprises make use of in determining the distinguishing differences with rivalgoods and services. Advertisement, one of the biggest factors in formation of purchasingbehaviours of today?s consumer, serves a lot to form a brand and positive attitudes towardsthe brand. It is an undisputable reality that use of all elements have special importance in theadvertising work to achieve this. Considering the process of formation of a brand and itsimage as a brand, first of all, it is necessary to locate precisely, the brand in the consumer?smind. It is advertising that determines the progress and speed of this process. Besidesrealising the final objective expected from advertising, implementation performed taking intoconsideration the level of consumer attitudes, habits and expectations towards the brand, willmake it easier to locate the brand in consumer?s mentality. To this end, the brand loyalty, theenterprises are trying to attain upon target groups via advertising, their support towards thebrand attitude formation process and the strong brands to be formed in the end of this effort,will turn out to be a direct advertising. In this research, studying the role of advertisements indetermining the consumer behaviours, it has been tried to search the contribution ofadvertisement strategies to be implemented, to the formation of a brand.Keywords: Brand, Consumer, Advertising.
The place of advertisement in the trademark formation
Keywords: İletişim Bilimleri; Radyo-Televizyon